Large-Scale Education Reform in General Equilibrium: Regression Discontinuity Evidence from India - Khanna, Gaurav (Journal of Political Economy, 2023)
The economic consequences of large-scale government investments in education depend on general equilibrium effects in both the labor market and the education sector. I develop a general equilibrium model capturing the consequences of massive countrywide schooling initiatives. I provide unbiased estimates of the model’s elasticities, using a regression discontinuity derived from Indian government policy. The earnings returns to a year of education are 13.4%, and the general equilibrium labor market effects substantially depress returns, by 6.6 percentage points. These general equilibrium effects have distributional consequences across cohorts and skill groups, whereby unskilled workers are better off and skilled workers worse off.